2016
DOI: 10.1530/erc-15-0162
|View full text |Cite
|
Sign up to set email alerts
|

MAPK and SHH pathways modulate type 3 deiodinase expression in papillary thyroid carcinoma

Abstract: Type 3 deiodinase (DIO3, D3) is reactivated in human neoplasias. Increased D3 levels in papillary thyroid carcinoma (PTC) have been associated with tumor size and metast atic disease. The objective of this study is to investigate the signaling pathways involved in DIO3 upregulation in PTC. Experiments were performed in human PTC cell lines (K1 and TPC-1 cells) or tumor samples. DIO3 mRNA and activity were evaluated by real-time PCR and ion-exchange column chromatography respectively. Western blot analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…The crosstalk between the SHH and MAPK pathways for D3 upregulation has also been demonstrated in human PTC cell lines (Romitti et al 2012(Romitti et al , 2016. Similarly, D3 depletion reduces cell proliferation and decreases cyclin D1 levels (Romitti et al 2016). Taken together, these data support the link between D3 overexpression and SHH/ Gli2 pathway reactivation, suggesting that decreased intracellular levels of THs may be a critical factor for tumor growth, at least in some types of cancer.…”
Section: Pi3k/protein Kinase B Pathwaysupporting
confidence: 61%
See 3 more Smart Citations
“…The crosstalk between the SHH and MAPK pathways for D3 upregulation has also been demonstrated in human PTC cell lines (Romitti et al 2012(Romitti et al , 2016. Similarly, D3 depletion reduces cell proliferation and decreases cyclin D1 levels (Romitti et al 2016). Taken together, these data support the link between D3 overexpression and SHH/ Gli2 pathway reactivation, suggesting that decreased intracellular levels of THs may be a critical factor for tumor growth, at least in some types of cancer.…”
Section: Pi3k/protein Kinase B Pathwaysupporting
confidence: 61%
“…In an opposite manner, miR21 positively regulates D3 expression in BCC through grainyhead-like 24:11 transcription factor 3 (GRHL3) (Di Girolamo et al 2016). The crosstalk between the SHH and MAPK pathways for D3 upregulation has also been demonstrated in human PTC cell lines (Romitti et al 2012(Romitti et al , 2016. Similarly, D3 depletion reduces cell proliferation and decreases cyclin D1 levels (Romitti et al 2016).…”
Section: Pi3k/protein Kinase B Pathwaymentioning
confidence: 81%
See 2 more Smart Citations
“…The extent of thyroid metabolic function is reflected in the levels of circulating T3 and thyroglobulin, upon which the intrathyroid redox status is dependent. Romitti et al (2016) demonstrated that the increase in circulating T3 is caused by higher deiodinase activity in PTC. Larger goiters that have a tendency to grow and to acquire retrosternal position are characterized by increased oxidants production, whereas the negative correlation between TAS and goiter size reveals the importance of appropriate antioxidant capacity in the prevention of goiter growth.…”
Section: Discussionmentioning
confidence: 99%